Evaluating Pleurotus ostreatus growth for upcycling textile waste from the fashion industry - Ian A. Fletcher (Frontiers in Sustainability)
The fast fashion industry’s rapid growth has led to about 92 million tons of textile waste each year and contributes 10% of global carbon emissions, which is expected to rise by 50% by 2030. This study examines a sustainable method for upcycling textile waste using the edible mushroom Pleurotus ostreatus. Thirteen fabric substrates, consisting of both natural and synthetic fibers, were cultivated on four growth media—malt extract agar (MEA), malt extract yeast agar (MYA), potato dextrose agar (PDA), and potato dextrose yeast agar (PDYA)—to assess their effectiveness in supporting mycelium growth, morphological characteristics, and biomass yield. Results showed that all fabric substrates supported mycelium growth, with MEA, MYA, and PDYA emerging as the most effective growth media. PDYA produced the highest biomass yield, highlighting its potential for upcycling applications. Statistical analysis demonstrated the significant effect of growth media on the lag and exponential growth phases, underscoring the importance of nutrient-rich environment conditions for optimized growth. This study confirms the viability of utilizing Pleurotus ostreatus mycelium for transforming textile waste, with the potential to provide an innovative and eco-friendly approach to reducing the fashion industry’s environmental footprint.